2003
DOI: 10.1099/jmm.0.04949-0
|View full text |Cite
|
Sign up to set email alerts
|

Species prevalence and antibacterial resistance of enterococci isolated in Kuwait hospitals

Abstract: This study investigated the species prevalence and antibacterial resistance among enterococci isolated in Kuwait hospitals. They consisted of 415 isolates of Enterococcus faecalis (85·3 %), Enterococcus faecium (7·7 %), Enterococcus casseliflavus (4·0 %), Enterococcus avium (1·2 %), Enterococcus durans (1·0 %), Enterococcus gallinarium (0·5 %) and Enterococcus bovis (0·2 %) isolated from urine (36·6 %), blood (10·4 %), wound swabs (11·0 %), stool samples (12·0 %), high vaginal swabs (9·0 %), endocervical swabs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
49
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 25 publications
14
49
0
Order By: Relevance
“…The predominant species of Enterococci isolated in the present study was Enterococcus faecalis 34/45 (75.60%) followed by Enterococcus.faecium 5/45 (11.10%). Similar observations were reported by various workers (14,15,18). In the present study E.columbae, E.durans, E.canis and E.sulfureus were also isolated.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The predominant species of Enterococci isolated in the present study was Enterococcus faecalis 34/45 (75.60%) followed by Enterococcus.faecium 5/45 (11.10%). Similar observations were reported by various workers (14,15,18). In the present study E.columbae, E.durans, E.canis and E.sulfureus were also isolated.…”
Section: Discussionsupporting
confidence: 79%
“…Isolation of Enterococci predominantly from urine has also been reported from various studies also. (15,18) The most probable reason for high isolation rate of Enterococci from UTI cases could be due to the close proximity of anal opening to urethra as Enterococci reside as commensals in GIT. Urinary catheterization as required in some cases may also have contributed to higher isolation of Enterococci from urine specimens.…”
Section: Discussionmentioning
confidence: 99%
“…In this study the prevalence of vanC phenotype enterococci was significantly higher (23.7% of E. gallinarum and 5.2% of E. casseliflavus) than in several studies that reported intestinal colonization by enterococci vanC. In 1997, the prevalence of colonization by these species in another hospital in Brazil was 1.2% (Cereda et al 1997), Canada presented 5% of these species (Toye et al 1997), Lebanon 1.4% (Zouain & Araj 2001), and Kuwait 4.5% (Udo et al 2003). The high prevalence obtained in this study is very important because several studies have reported infection or colonization by E. gallinarum carrying genes that determine high resistance to vancomycin: E. gallinarum vanA in Belgium (Dukta-Malen et al 1994), in Italy (Biavasco et al 2001), in Japan (Takayama et al 2003), and in Brazil (Camargo et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[2] Vancomycin resistance among Enterococcus isolates is a major problem in most of the western world, especially in the United States where according to the National Nosocomial Infections Surveillance(NNIS) data [3] Some of the adverse outcomes associated with the infections caused by VRE are extended length of hospital stay, increased cost and increased mortality. [4] Thus, our study is to find out the vancomycin resistant strains of E. faecalis from dental caries population.…”
Section: Introductionmentioning
confidence: 99%
“…this species in root canal treated patients evidenced by culturing methods, and molecular detection tools suggested that it may be the reason for most of Vancomycin resistance oblem in most of the western world, especially in the United States where according to the National Nosocomial Infections Some of the adverse outcomes associated with the infections caused by VRE are extended stay, increased cost and increased mortality. [4] Thus, our study is to find out the vancomycin resistant strains of E. faecalis from dental caries population.…”
Section: Introductionmentioning
confidence: 99%